Prohibition of Abortion as a Violation of Women's Human Rights Under International Legal Standards in the ICCPR and CEDAW - Quddus, Muh. Syah; Permatasari, Tia; Nafitabella, Syfa Aswa; Pertiwi, Raja Rasih Harianty Andina (Indonesian Journal Publisher, 2025)
Reproductive rights related to access to safe and legal abortion are an important issue in women's human rights discussions at the global level because they involve the right to health, safety and bodily autonomy. Although international laws such as the ICCPR and CEDAW guarantee this right, many countries still impose strict bans or restrictions on abortion, which often contradict basic human rights principles. This research aims to analyze women's human rights violations resulting from abortion bans and evaluate state obligations under the ICCPR and CEDAW standards. This research uses a normative juridical approach by analyzing secondary data from primary, secondary, and tertiary legal materials. The research findings show that reproductive rights are an integral part of women's human rights as stipulated in various international legal instruments, such as the International Covenant on Civil and Political Rights (ICCPR) and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Although this right has been juridically recognized, its implementation in many countries still faces significant obstacles, especially in access to safe abortion, which is often restricted by discriminatory regulations. Such restrictions not only violate the principles of non-discrimination and gender equality, but can also be categorized as inhumane treatment, and prevent women from accessing reproductive health services equally and with dignity as guaranteed by international law. Therefore, countries are obliged to reform national laws and ensure that reproductive health policies respect women's rights, and are supported by strong international oversight based on human rights principles.